Acute ST segment elevation MI with Normal Coronaries - Barakoti, M; Jha, SC; Acharya, SM; Paudel, CM (Nepalese Heart Journal, 2013)
A 45 year-old man with no history of cardiac disease presented to the emergency department with typical angina chest pain of >24 hours duration. He was not thormbolyzed due to late presentation. Having elevated troponin and CK-MB levels and an electrocardiogram demonstrating anterolateral ST segment elevation and persistent of angina pain prompted coronary angiography which could be done only after 3 weeks of symptom onset due to financial constraint; which revealed coronary vessels free of significant disease. An echocardiogram showed dilatation of all cardiac chambers with hypokinesia of anterior wall and mid-septum and akinesia of apex. There was moderate mitral regurgitation and moderate tricuspid regurgitation and moderate systolic dysfunction. A number of conditions can lead to ST segment elevation MI with normal epicardial coronary anatomy. We report a case possibly due to autothrombolysis. Treatment to such cases would be symptomatic drug therapy with reassurance and risk factor reduction. DOI: http://dx.doi.org/10.3126/njh.v8i1.8335 Nepalese Heart Journal Vol.8(1) 2011 pp.33-36